Pertumbuhan Tanaman Nanas pada Berbagai Konsentrasi IBA Secara In Vitro - Zarmiyeni Zarmiyeni; Siti Munawarah Munawarah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2014)
The people of Hulu Sungai Utara Regency are very fond of pineapple, this can be seen from the continued increase in market demand for pineapple. Pineapple production in Hulu Sungai Utara Regency from 2010-2013 continues to increase. However, the availability of pineapple is still widely supplied from other regions. This is due to limited land and the availability of superior seeds. Therefore we need a new technique to overcome this problem by multiplying it in vitro. This study aims (i) to determine the response of pineapple plant growth to various concentrations of IBA (Indole Butyric Acid) in vitro and (ii) to obtain the best IBA (Indole Butyric Acid) concentration for pineapple plant growth in vitro. The study was conducted in the Amuntai STIPER tissue culture laboratory from March to June 2014, using a Completely Randomized Design (CRD) with 5 treatment levels, 4 replications. The factor tested was the IBA concentration, i1 = 1.5 ppm, i2 = 2 ppm, i3 = 2.5 ppm, i4 = 3 ppm, and i5 = 3.5 ppm. The results showed no known response and the best concentration of IBA on pineapple plant growth.